ICT Usages in Yogyakarta's Tourist Villages Development - Choirunnisa, Ulfah; Rachmawati, Rini (Graduate School, Universitas Brawijaya, 2020)
Developmental gap between tourist villages occurs due to differences in tourist attractions, existing facilities, and also the use of Information, Communication, and Technology (ICT). One of the innovations which is presently in line with global development is the use of information technology. This study was aimed at identifying the development of 17 tourist villages using the Butler Tourist Area Life Cycle Theory, determining the use and needs of ICT in tourist villages using the Smart Tourism Destinations Theory, and analyzing the role of ICT in developing tourist villages in the City of Yogyakarta. The results of this study indicated that the dynamics of the development of tourist villages were caused by several factors: availability of human resources, the potential of tourist villages, and tourism awareness of tourist village communities. Besides, the use of ICT in the villages was limited to wi-fi usage and the use of social media such as Facebook and Instagram. Lastly, the role of ICT actively by managers and passively by tourists was able to accelerate the development of tourist villages.Keywords: ICT, Tourist villages.